Determination of Histidine Protonation States in Proteins by Fast Magic Angle Spinning NMR - Zadorozhnyi, Roman; Sarkar, Sucharita; Quinn, Caitlin M.; Zadrozny, Kaneil K.; Ganser-Pornillos, Barbie K.; Pornillos, Owen; Gronenborn, Angela M.; Polenova, Tatyana (Frontiers in Molecular Biosciences, 2021)
Histidine residues play important structural and functional roles in proteins, such as serving as metal-binding ligands, mediating enzyme catalysis, and modulating proton channel activity. Many of these activities are modulated by the ionization state of the imidazole ring. Here we present a fast MAS NMR approach for the determination of protonation and tautomeric states of His at frequencies of 40-62 kHz. The experiments combine 1H detection with selective magnetization inversion techniques and transferred echo double resonance (TEDOR) – based filters, in 2D heteronuclear correlation experiments. We illustrate this approach using microcrystalline assemblies of HIV-1 CACTD-SP1 protein.